Support from the national extension service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Can agricultural extension services have a role in helping farmers with marketing? In Cameroon the answer is ?Yes?. A government marketing adviser describes the methods he uses to link farmers to buyers, and make their products more marketable.